2019
DOI: 10.1017/s0033291719001971
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of sex differences in PTSD symptoms across development: evidence from the ALSPAC cohort

Abstract: BackgroundCross-sectional evidence suggests females in late adolescence exhibit higher rates of post-traumatic stress symptoms (PTSS) than males and younger age groups. However, longitudinal evidence is limited, and underlying factors are not well understood. We investigated the emergence of sex differences in PTSS from childhood to adolescence in a large, longitudinal UK cohort, and tested whether these could be explained by overlap between PTSS and depressive symptoms, or onset of puberty.MethodsTrauma expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
2
19
3
Order By: Relevance
“…In particular, 28.9% of all of the respondents reported moderate to high SRs, and 5.8% of adolescents reported the presence of five or six behaviors with a very high frequency rate. Females reported SRs 2.5 times more than males, according to research that found that females show higher levels of SRs in adolescence (Haag et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 28.9% of all of the respondents reported moderate to high SRs, and 5.8% of adolescents reported the presence of five or six behaviors with a very high frequency rate. Females reported SRs 2.5 times more than males, according to research that found that females show higher levels of SRs in adolescence (Haag et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Results from a large meta-analysis of 64 studies found that female sex became a stronger risk factor as age increased, based on samples of children aged 6–18 years (Trickey et al, 2012 ). Similarly, longitudinal data from the UK ALSPAC cohort evidenced higher levels of PTSD symptoms in females versus males at ages 13 and 15 years, but not at ages 8 and 10 years (Haag et al, 2020 ). The emergence of sex differences throughout development suggests that the mechanism of PTSD formation may potentially be explained through changes in neuroendocrine, hormonal and stress response systems that are naturally affected during puberty (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…One recent epidemiological study of mental disorders in China also found higher prevalences of depressive (males 3.0% vs. females 4.2%) and anxiety disorders (including PTSD in that survey) (males 4.8% vs. females 5.2%) among females in a nationally representative sample ( Huang et al, 2019 ), although these gender disparities were not as large as those previously reported in other countries ( Kessler et al, 1994 , 1995 ). These gender differences exist at not only the diagnostic level but also the symptomatic or subclinical level ( Haag et al, 2019 ). Regarding HCWs who have been reported with higher prevalences of MHPs than the general population ( Kim et al, 2018 ; Wang et al, 2011 ), being female has also been found as a risk factor for the development of these problems ( Guille et al, 2017 ; Kim et al, 2018 ; MacGregor et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%